Analysis of Implementation of PSAK No. 46 Concerning Taxes Income in The Financial Statements of PT. Garuda Indonesia (Persero) Tbk Which Is Listed on The BEI Period 2021-2023 - Agung Supriyadi; Aan Kanivia; Ade Elza Surachman; Safitri Akbari; Dessy Kumala Dewi (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
PT. Garuda Indonesia (Persero) Tbk after the Covid-19 pandemic had an impact on the aviation industry. The decline in the number of passengers and income has had various impacts in terms of tax administration. This research aims to understand more deeply the application of accounting standards in companies, as well as ensuring compliance and quality of financial reporting in accordance with tax regulations. This research uses quantitative descriptive methods to reveal facts, circumstances, phenomena, variables and situations that occurred during the research, and presents them as they are. The research results show that PT. Garuda Indonesia (Persero) Tbk has implemented PSAK No. 46 concerning Income Tax, which covers temporary and permanent differences that arise in financial statements. Implementation of PSAK No. 46 at PT. Garuda Indonesia is in compliance with applicable tax regulations and has an impact on PT's financial statements. Garuda Indonesia (Persero) Tbk for the 2021-2023 period which includes four main aspects, namely recognition, measurement, presentation and disclosure. This has implications for PT's financial statements. Garuda Indonesia (Persero) Tbk complies with applicable accounting standards, so that it can increase transparency and quality of financial reporting, as well as assist in making strategic decisions related to income tax planning and management.